What to eat. the terapeutic and dietetic compliance of patients on peritoneal dialysis. - F. Pasticci; A. Selvi; M.T. Benedetto; A. Zuccalà (The Korean Society of Nephrology, 2012)
Nutrition education is important for patients on peritoneal dialysis. Yet, despite initial nutrition training and monthly reinforcements during follow-up visits, phosphorus control remains unsatisfactory. For this reason a meeting with an external renal dietician open to patients and their relatives was organized. Biographical data and average phosphorus levels for the 3 months prior to the meeting are shown in Table.1 Patients 11 (6 F - 5 M) Age (years) 63 (47-81) Time on Dialysis (months) 72 (6-348) Body Mass Index (kg/m2) 25.8 (22.3-32.4) Phosphorous mg/dl (average of 3 months) 5.95 (3.9-8.2)After a lecture delivered by the centre's nephrologist, a questionnaire on phosphorus control was compiled by the participants. The renal dietician then explained how to: control dietary phosphorous intake, properly use chelating agents, reduce phosphorous in cooking and make smart food choices. A trained chef then demonstrated how to cook some regional recipes specifically reworked to reduce their phosphorous content without sacrificing taste. Participants then verified that the recipes were indeed appetizing. At this point, the same questionnaire given at the start of the meeting was re-given. From this, an improvement in the understanding of phosphorus control was seen. For example, in response to the question "Who is responsible for controlling phosphorus?" the percentage of patients correctly answering "the patient" rose from 55% before the meeting to 91% after the meeting. To successfully manage kidney disease patients and their relatives need to understand how to best control for phosphorous and this can only be done through continuous nutrition education. The Authors are waiting on the results of phosphorus levels for the next 3 months. The Authors would like to thank Baxter Healthcare for its organizational support.